72.6k views
3 votes
Is the expression X space logical or space (Y space logical and space Z )equivalent to (X space logical or space Y )space logical and space (X space logical or space Z )for all possible inputs of X, Y, and Z

User Bukes
by
5.2k points

1 Answer

5 votes

Answer:

To prove:

X+Y.Z=(X+Y).(X+Z)

Taking R.H.S

= (X+Y).(X+Z)

By distributive law

= X.X+X.Z+X.Y+Y.Z --- (1)

From Boolean algebra

X.X = X

X.Y+X.Z = X.(Y+Z)

Using these in (1)

=X+X(Y+Z)+Y.Z

=X(1+(Y+Z)+Y.Z --- (2)

As we know (1+X) = 1

Then (2) becomes

=X.1+Y.Z

=X+Y.Z

Which is equal to R.H.S

Hence proved,

X+Y.Z=(X+Y).(X+Z)

User Aco
by
4.7k points